If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2 = 5x + 8 Reorder the terms: -2 + 2x = 5x + 8 Reorder the terms: -2 + 2x = 8 + 5x Solving -2 + 2x = 8 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + 2x + -5x = 8 + 5x + -5x Combine like terms: 2x + -5x = -3x -2 + -3x = 8 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + -3x = 8 + 0 -2 + -3x = 8 Add '2' to each side of the equation. -2 + 2 + -3x = 8 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 8 + 2 -3x = 8 + 2 Combine like terms: 8 + 2 = 10 -3x = 10 Divide each side by '-3'. x = -3.333333333 Simplifying x = -3.333333333
| 12x+17=13x+1 | | -7x-9=-23 | | w^2-7w-110=0 | | -12+3/4x=3 | | 4n+14=6n | | 5g+4y(-5+3g)=16g | | 9x+11=-1x-5 | | 12(x+2)=2(6x-4)+32 | | 7(2c-5)=25 | | -7392(18x-172)=0 | | 2x+3=2x-(3x+2)+6 | | c-4=18 | | 8x+3=3*2x-1 | | (6-x^2)-(36+12x+x^2)= | | (14+a)+16= | | w+-19=79 | | 6(3x+5)=2(6x-21)+6x | | 3=-5n+2 | | x^2-13x+53=17 | | 5+4x=-11x | | 12x+2=2(6x-4)+32 | | 54=2x^2-3x | | (-7)+7=0 | | 36a^2-12a+1= | | 5(3-2x)=3-4x | | -7921+15(198x-178)=0 | | y=4(3)-9 | | 5(7+8r)-2r=-9-6r | | -40-8a=-4(5a+7) | | 8-9x-2=-52+5x-12 | | 8y-(2y-3)=4 | | 7[3-4*(x+1)]+6[(2x+7)-8]=17x-333 |